Role of Phonophoresis in Management of Adhesive Capsulitis (Frozen Shoulder) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
This prospective study was performed in the department of Physical Medicine, Dhaka Medical College Hospital (DMCH), Dhaka for a period of 6 months to see the effect of phonophoresis (Ultrasound therapy with Naproxen gel) on adhesive capsulitis. During this period 240 (4% of total patients) patients were diagnosed as adhesive capsulitis of shoulder in outpatient department, Physical Medicine, Dhaka Medical College Hospital. Sixty patients were selected for the study and divided them into two groups. In group A, patients were treated with phonophoresis and exercises in contrast with group B patients who were treated with same exercises without phonophoresis for same duration. Patients in both groups were followed up weekly for consecutive six weeks. The mean age of the patients in this study was 51.73 ± 10.01 year, with a range of 35 to 70 years. Out of sixty patients 31 (51.7%) were male and 29 (48.3%) were female. The male: female ratio was 1.07: 1. Among 60 patients, 27 (45%) were housewives, 20 (33.3%) service holders (official job), 4 (6.7%) businessmen, 1 (1.7%) teacher and 8 (13.3%) retired persons. In this study 53.3% patients had right shoulder involvement and rest of them (46.7%) had left sided involvement. Pain was improved just after initiation of treatment and it was completely alleviated in group A patients after 6th week, on the contrary although pain was increased after 1st week of treatment thereafter it was gradually decreased but it was not completely alleviated in group B patients at the end of the study. All sorts of range of motions (abduction, internal rotation on abduction, external rotation on abduction) of affected shoulder were improved more rapidly in group A compared to group B patients. Shoulder pain and disability index (SPADI) were significantly reduced in group A compared to group B patients.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21057